The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.2169/internalmedicine.50.4627
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Propofol Sedation for Endoscopic Submucosal Dissection (ESD): Assessment with Prospective Data Collection

Abstract: Objective The indications for endoscopic treatment in early stage cancer of the digestive tract are expanding with the emergence and technical development of endoscopic submucosal dissection (ESD). ESD requires longer term stable sedation than conventional endoscopic procedures due to the necessity of meticulous control of the devices during the procedure. Propofol has a very short half-life and can be administered continuously, which is advantageous for long-term sedation. Propofol, thus, is likely to be usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 24 publications
2
42
1
1
Order By: Relevance
“…Propofol is a short-acting sedative, with a plasma half-life of only 1-4 min, which is considerably lesser than that of a benzodiazepine. Kiriyama et al [1] and Yamagata et al [2] reported that patients who underwent ESD with propofol sedation had a quicker recovery profile than those who underwent ESD with midazolam sedation. Propofol is considered a useful drug because the quick recovery from its sedation may decrease the incidence of aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propofol is a short-acting sedative, with a plasma half-life of only 1-4 min, which is considerably lesser than that of a benzodiazepine. Kiriyama et al [1] and Yamagata et al [2] reported that patients who underwent ESD with propofol sedation had a quicker recovery profile than those who underwent ESD with midazolam sedation. Propofol is considered a useful drug because the quick recovery from its sedation may decrease the incidence of aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the usefulness of various sedation methods for ESD has been reported [1,2,3]; however, major critical complications after ESD such as perforation and bleeding have also been reported; perforation and postoperative bleeding occurred in 2-4% and 4-6% of cases, respectively [4,5,6,7,8]. Furthermore, aspiration pneumonia, venous thrombosis and phlegmonous gastritis have been reported as rare complications of ESD [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…An analgesic (pentazocine, 7.5-15 mg) was given intravenously at the beginning of sedation and further injection was performed depending on the patient's condition. When the combination of propofol and pentazocine could not achieve or maintain an adequate level of sedation, droperidol was added [15] .…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…12,13 However, this agent occasionally decreases systemic vascular resistance, cardiac contractility, and ultimately cardiac output without a concomitant change in heart rate, and respiratory depression can also occur. 5,14,15 Recently, several studies have revealed most adverse events associated with propofol sedation were mild and often transient during advanced interventional endoscopic procedure. 12,[16][17][18] A randomized study in Japan, which compared continuous propofol infusion with intermittent midazolam injection during ESD for EGC, found that propofol is a safe and effective sedative agent and that patients treated with propofol had a quicker recovery than those who were treated with midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of studies for propofol sedation during ESD by nonanesthesiologist have proven that propofol sedation has similar safety profile compared to conventional sedation with midazolam. 3,5,6 In these studies, propofol was administrated in bolus or by continuous infusion, and target sedation level was mostly moderate sedation. However, intermittent bolus injection of propofol may be theoretically associated with fluctuation of plasma concentration.…”
Section: Introductionmentioning
confidence: 99%